2021
DOI: 10.1021/acssuschemeng.0c07607
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating Nanodiamonds from Biomass by Direct Laser Writing under Ambient Conditions

Abstract: Commercial nanodiamonds (NDs) are usually produced by detonation and chemical vapor deposition. While these methods normally require either the application of extreme temperatures/pressures or expensive and hazardous gaseous/ chemical precursors, in this study, NDs were produced on paper made from nanolignin/cellulose nanofibrils (LCNF) composite film by means of direct laser writing at ambient temperature and air pressure. The generation of NDs was found to depend largely on high laser power. Graphene nanorib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 73 publications
3
11
0
Order By: Relevance
“…This transformation phenomenon was also observed in our previous research on the formation of NDs from LCNFs. 16 The generation of NDs from nanolignin was found at 900 mW in this study, much higher than that from LCNFs at 600 mW. This confirmed our inference about the positive role of cellulose nanofibrils in the biomass−ND conversion.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…This transformation phenomenon was also observed in our previous research on the formation of NDs from LCNFs. 16 The generation of NDs from nanolignin was found at 900 mW in this study, much higher than that from LCNFs at 600 mW. This confirmed our inference about the positive role of cellulose nanofibrils in the biomass−ND conversion.…”
Section: Resultssupporting
confidence: 89%
“… 24 , 25 , 32 It is impressive that we have fabricated circuit patterns from nanolignin/cellulose nanofibril composites, showing promising applications as flexible electrics and sensors. 16 Since the patterns in this study contained graphene and ND microstructures and showed varying degrees of resistances in the following discussion, it was reasonable that these patterns can be applied for fabricating electric devices.…”
Section: Results and Discussionmentioning
confidence: 86%
See 3 more Smart Citations